Economic Potential and Business Development Strategy of Oil Palm Frond Waste Utilization in Rokan Hilir Regency, Indonesia - Junaidi Junaidi; Suhendri Suhendri; Zulham Zulham; R.Turino Januar Budyanto (SEAN Institute, 2026)
This study evaluates the economic potential and strategic options for utilizing oil palm frond waste as an additional source of income for farmers and communities living around the plantation. The research was conducted from June to August 2026 at the Sei Meranti Estate of PT Perkebunan Nusantara IV, Meranti Makmur Village, Rokan Hilir Regency, Riau Province. A descriptive mixed-methods design was employed. The study involved 65 respondents, selected using the Slovin formula and proportionate stratified random sampling, together with eight key informants chosen through purposive sampling. Data were collected through observation, questionnaires, interviews, documentation, and a literature review. The analytical procedures included descriptive analysis, cost and revenue analysis, income analysis, the revenue–cost ratio, income contribution analysis, and SWOT analysis using the IFAS and EFAS matrices. The findings indicate that 60% of respondents reported that oil palm fronds were still arranged between planting rows and had not yet been processed into commercial products. Fermented animal feed emerged as the most promising alternative, generating a net income of IDR 4,500,000 per month, an R/C ratio of 1.75, and an income contribution of 8.57%. The SWOT analysis positioned the business development strategy in Quadrant I. The priority strategies include establishing a group-based business unit, providing processing training, procuring shredding machinery, standardizing production processes, conducting market trials, and strengthening collaboration among the company, the Village-Owned Enterprise (BUMDes), the village government, and local livestock farmers.